Preventing Classroom Discipline Problems: A Classroom Management Handbook - Seeman, Howard (Rowman & Littlefield Publishers, 1999)
ORDER 10 OR MORE OF ANY ITEM AND RECEIVE A 20% DISCOUNT! Preventing Classroom Discipline Problems is a handbook, with its own self-improvement exercises, for all the skills needed to implement successful classroom management and eliminate discipline problems. It features a unique training video and CD both cued to the book for: education workshops, administrators, teachers, and education students. The video can be shown at faculty meetings, education workshops, classes, etc., and the CD can be used for independent training at each student or teachers' private computer. With access to Online, Confidential Help, and a professional seminar, from the author, a national consultant on Classroom Management, at: http://www.ClassroomManagementOnline.com/ The video/CD demonstrates both the ineffective and effective teacher with real classroom discipline problems. These scenes are spontaneously acted out by real teachers and student-teachers. Instead of following a written script, they act out how their real disruptive students would actually behave, and what they, the teachers, would actually say in these classroom situations. If "the teacher" in the scene does something that is ineffective, what you will see is how their real students would actually respond. If, on the other hand, the teacher is effective, then you'll see how their real students would actually change their behavior. These materials (book, video, CD) do not just help with handling discipline problems, but also help educators diagnose the causes of discipline problems, and thereby help with the prevention of disruptive behavior (rather than just controlling discipline problems) for more effective classroom management. All the suggestions can be implemented without asking educators to change their personal teaching styles, and without the need for a school to revamp its entire program (as some discipline programs require). The book and video/CD can be used by individual teachers and administrators who wish to cut down on referrals to the of